Beyond web/native/hybrid: a new taxonomy for mobile app development - Nunkesser, Robin (2018 IEEE ACM 5th International Conference on Mobile Software Engineering and Systems (MOBILESoft), 2018)
Currently, mobile operating systems are dominated by the duopoly of iOS and Android. App projects that intend to reach a high number of customers need to target these two platforms foremost. However, iOS and Android do not have an officially supported common development framework. Instead, different development approaches are available for multi-platform development. The standard taxonomy for different development approaches of mobile applications is: Web Apps, Native Apps, Hybrid Apps. While this made perfect sense for iPhone development, it is not accurate for Android or cross-platform development, for example. In this paper, a new taxonomy is proposed. Based on the fundamental difference in the tools and programming languages used for the task, six different categories are proposed for everyday use: Endemic Apps, Web Apps, Hybrid Web Apps, Hybrid Bridged Apps, System Language Apps, and Foreign Language Apps. In addition, when a more precise distinction is necessary, a total of three main categories and seven subcategories are defined. The paper also contains a short overview of the advantages and disadvantages of the approaches mentioned.